The Concept of Adolescent Mental Health from an Islamic Perspective - Nur Ihwana; Rosdialena (Journal Of Psychology, Counseling And Education, 2026)
Mental health is a condition that enables individuals to function optimally in their daily lives, emotionally, psychologically, and socially. During adolescence, mental health becomes a crucial aspect because this stage is characterized by various physical, emotional, and social changes that influence how adolescents think, feel, and behave. From an Islamic perspective, mental health is not only related to psychological well-being but also encompasses a harmonious relationship with Allah SWT, fellow human beings, and the surrounding environment. This article examines the concept of adolescent mental health from an Islamic perspective and explores efforts to maintain and improve mental well-being based on the teachings of the Qur’an and Sunnah. The method used is library research by utilizing various sources, including books, scientific journals, articles, and other relevant literature. The findings indicate that adolescent mental health in Islam can be achieved through strengthening faith, consistently performing acts of worship, developing self-control, coping with life’s challenges, and adapting to ongoing changes. Furthermore, adolescents with good mental health are able to build positive social relationships, manage their emotions wisely, and develop their potential optimally. Therefore, Islamic values can serve as an important foundation for fostering balanced and sustainable mental health among adolescent.